2003
DOI: 10.1007/s00441-002-0674-0
|View full text |Cite
|
Sign up to set email alerts
|

The expression pattern and assembly profile of synaptic membrane proteins in ribbon synapses of the developing mouse retina

Abstract: In the present study, we generated a systematic overview of the expression pattern and assembly profile of synaptic membrane proteins in ribbon synapses of the developing mouse retina. Using indirect immunofluorescence microscopy, we analyzed the spatial and temporal distribution of 11 important membrane and membrane-associated synaptic proteins (syntaxin 1/3, SNAP-25, synaptobrevin 2, synaptogyrin, synaptotagmin I, SV2A, SV2B, Rab3A, clathrin light chains, CSP and neuroligin I) during synaptogenesis. The temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 100 publications
5
26
1
1
Order By: Relevance
“…Our anatomical data are in line with developmental findings suggesting that photoreceptor terminals first acquire basic synaptic properties during the first postnatal week, before becoming ribbon synapses during the second postnatal week [32] and completing their maturation after eye opening [54].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our anatomical data are in line with developmental findings suggesting that photoreceptor terminals first acquire basic synaptic properties during the first postnatal week, before becoming ribbon synapses during the second postnatal week [32] and completing their maturation after eye opening [54].…”
Section: Resultssupporting
confidence: 90%
“…The rabbit anti-VAMP2 (Abcam) reacts with a single 19 kDa band (manufacturer's technical information). The expression pattern obtained here was consistent with previous reports [32].…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Close observation of the direct-contact pattern showed that the inner part of the graft retina (other than ONL) was being “stripped off,” or pushed aside, enabling the bare graft ONL cells to make a direct contact with host bipolar cells in the correct orientation (Figures S3A and S3A’). This could also imply that the graft photoreceptors in young grafts developed in a structured ONL/INL complex nearly to the stage of synaptogenesis (i.e., around postnatal days 4–7; von Kriegstein and Schmitz, 2003), but somehow they formed host-graft synapses instead of intragraft synapses that we also observed in the neighboring area of host-graft synaptogenesis (Figures S4E–S4J). In some host-graft border area, both the host and graft bipolar cells sent dendrite terminals over the graft photoreceptor terminals of the same area.…”
Section: Discussionmentioning
confidence: 78%
“…A recent developmental study of synaptic vesicle protein expression in the mouse retina as assessed by immunohistochemistry compares favourably with our data (Kriegstein & Schmitz, 2003). Analogous to the development of the cerebellar cortex, the early postnatal retina comprises layers of neuronal precursors that migrate and differentiate to form distinct layers of neurons and synapses, with the majority of synaptogenesis occurring in the second postnatal week (Olney, 1968).…”
Section: Csp Is Phosphorylated On Ser 10 In Vivomentioning
confidence: 99%